The EC4 European syllabus for post-graduate training in clinical chemistry and laboratory medicine: Version 4-2012 - Wieringa, G.; Zerah, S.; Jansen, R.; Simundic, A.-M.; Queralto, J.; Solnica, B.; Gruson, D.; Tomberg, K.; Riittinen, L.; Baum, H.; Brochet, J.-P.; Buhagiar, G.; et al. (Clinical Chemistry and Laboratory Medicine, 2012)
Laboratory medicine's practitioners across the European community include medical, scientific and pharmacy trained specialists whose contributions to health and healthcare is in the application of diagnostic tests for screening and early detection of disease, differential diagnosis, monitoring, management and treatment of patients, and their prognostic assessment. In submitting a revised common syllabus for post-graduate education and training across the 27 member states an expectation is set for harmonised, high quality, safe practice. In this regard an extended 'Core knowledge, skills and competencies' division embracing all laboratory medicine disciplines is described. For the first time the syllabus identifies the competencies required to meet clinical leadership demands for defining, directing and assuring the efficiency and effectiveness of laboratory services as well as expectations in translating knowledge and skills into ability to practice. In a 'Specialist knowledge' division, the expectations from the individual disciplines of Clinical Chemistry/Immunology, Haematology/Blood Transfusion, Microbiology/Virology, Genetics and In Vitro Fertilisation are described. Beyond providing a common platform of knowledge, skills and competency, the syllabus supports the aims of the European Commission in providing safeguards to increasing professional mobility across European borders at a time when demand for highly qualified professionals is increasing and the labour force is declining. It continues to act as a guide for the formulation of national programmes supplemented by the needs of individual country priorities. © 2012 by Walter de Gruyter • Berlin • Boston.
Keywords: Competence to practice; Continuous professional development; Education; Leadership; Quality; Specialist in laboratory medicine; training